Urgenza climatica e ambientale, usurocrazia e debito dei paesi poveri (Stato, Chiese e pluralismo confessionale, 2024)
Climate and environmental urgency, usurocracy and poor countries' debtABSTRACT: This contribution, like other previous ones on the subject, is moved by the intent to acquaint readers of this informed scientific magazine with debates and updates intended for contexts other than canon law and state ecclesiastical law, but undoubtedly close in content and method of inquiry. These are the battles of civilization against the international imperialism of money, condemned by the Roman Pontiffs and in even more incisive tones by Pope Francis, to whom the following paper is dedicated on the occasion of his 87th birthday. Its remote origins are to be found in the struggles against usury of the Roman plebs, embraced by Simon Bolivar and his epigones. The author of the paper, Advocate of the Holy See for the Canonical and Civil Forum, reconnects with the great tradition in question when he returns to the subject of the foreign debt of poor countries, closely connected in our days with that of climate and environmental urgency. This is a new element, which enriches the acquisitions on the failures of debt and the financialization of the world economy with a deepening, from a legal point of view, of the holistic dimension of nature and the reality that surrounds us.SOMMARIO: 1. I quattro NO di Papa Francesco - 2. Dall’Italia al Burkina Faso al Sudafrica - 3. Il ruolo della Santa Sede: in particolare, Francesco e il Nord del mondo - 4. L’Enciclica Laudato si’ e l’Esortazione apostolica Laudate Deum.